HUBUNGAN USIA DENGAN JENIS HERNIA INGUINALIS DI RS PERTAMINA BINTANG AMIN LAMPUNG : Relationship Age and the Type of Inguinal Hernia at Pertamina Bintang Amin Hospital - Erianto, Mizar; Futri, Futri Nabilla; Triwahyuni, Tussy; Prasetia, Toni (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2021)
Hernia is a condition where part of the intestines comes out of the abdominal cavity to form a bulge that can be seen and felt from the outside. In general, people who have reached old age, hernia is a disease that often occurs at that age, because the smooth muscle wall of the abdomen weakens in old age, so it is very risky for hernias to occur. This disease is characterized by the protrusion of abdominal contents through a weak part of the abdominal wall, this disorder is mainly found in the groin area. Increasing a person's age has an impact on decreasing system function in the body so that they are more susceptible to various diseases. Increasing age is also closely related to the prognosis of a disease and life expectancy. This study aimed to determine the relationship between age and the type of inguinal hernia at Pertamina Bintang Amin Hospital Bandar Lampung in 2019-2020. This type of research was cross -sectional. Sampling was done by total sampling. Bivariate data analysis withtest Spearman's. Statistical analysis using thetest Spearman showed the p-value for the analysis of the relationship between age and the type of inguinal hernia was 0.033 (p-value < Â 0.05). There was a relationship between age and type of inguinal hernia at Pertamina Bintang Amin Hospital Lampung in 2019-2020. Health institutions should be able to provide counseling related to the relationship between old age and inguinal hernia and conduct early inguinal hernia screening to the public.